3407 Maternal Daytime Dysfunction Due to Sleepiness and its Relation to Child Psychopathology. (27th March 2019) - Strong, Cameron; Fitzgerald, Kate; Premo, Julie
Abstract : OBJECTIVES/SPECIFIC AIMS: Anxiety is prevalent in early childhood and, when left untreated, increases children's risk for chronic anxiety and depression later in life. Maternal risk factors (e.g. income and marital status) have also been shown to heighten their children's risk for the development of the aforementioned psychopathology. Sleep plays a critical role in behavior regulation, is affected in depression, and is influenced by a wide range of demographic and psychological variables. The purpose of this study was to examine the relationship between maternal sleep and the presence in their children of reported symptoms relating to anxiety, depression, and behavior regulation. METHODS/STUDY POPULATION: Children (n=59, aged: 4-9 years (M = 6.069, SD = 1.006, 59.3% female) and their mothers were sampled from clinic and community settings and were administered questionnaires. Maternal sleep quality was assessed by the Pittsburgh Sleep Quality Index, which captures both numeric and self-reported categories relating to an individual's perception of their sleep. Child anxiety and depression were assessed via parent-reported Child Behavioral Checklist (CBCL). Maternal depression symptoms were assessed with the Beck Depression Inventory (BDI). Associations between these measures were analyzed by ANOVA with post-hoc analysis and linear regression as appropriate. RESULTS/ANTICIPATED RESULTS: A statistically significant difference was observed in the mean child CBCL scores when children were sub-set into maternal categories of self-reported days of dysfunction due to sleepiness over the past month. Mean child CBCL T-score domains with statistically significant differences were: attention problems (F = 4.935, p = 0.004), depression problems (F = 3.073, p = 0.035), ADHD (F = 4.422, p = 0.007), oppositional defiant (F = 2.865, p = 0.045), and total t-score (F = 3.073, p = 0.035). Maternal mean DBI scores were also statistically significantly different when grouped by days of maternal dysfunction due to sleepiness (F = 9.791, p < 0.001). There was no relation between these CBCL categories and maternal DBI scores. DISCUSSION/SIGNIFICANCE OF IMPACT: Maternal self-reported days of dysfunction due to sleepiness may potentially increase risk for their children to develop further psychopathology independent of mothers' depression symptomatology. These findings highlight the need for broader assessment clinically of children's environments with additional focus on maternal function given the potential impact on their children's functional outcomes.